Mark Twain's book of animals - Twain, Mark, 1835-1910 (Twain, Mark, 1835-1910. Jumping frogs, 2010)
Longtime admirers of Mark Twain are aware of how integral animals were to his work as a writer, from his first stories through his final years, including many pieces that were left unpublished at his death. This beautiful volume, illustrated with 30 new images by master engraver Barry Moser, gathers writings from the full span of Mark Twain's career and elucidates his special attachment to and regard for animals. What may surprise even longtime readers and fans is that Twain was an early and ardent animal welfare advocate, the most prominent American of his day to take up that cause. Edited an.